Circadian and sex differences in carotid-femoral pulse wave velocity in young individuals and elderly with and without type 2 diabetes - Gentilin, Alessandro; Moghetti, Paolo; Cevese, Antonio; Mattioli, Anna Vittoria; Schena, Federico; Tarperi, Cantor (Frontiers in Cardiovascular Medicine, 2022)
The incidence of cardiovascular events is higher in the morning compared to the evening and differs between sexes. We tested the hypothesis that aortic stiffness, a compelling cardiovascular risk factor, is increased in the morning compared to the evening, in young healthy individuals between 18-30 years (H18-30) or in older individuals between 50-80 years, either healthy (H50-80) or with type 2 diabetes (T2DM50-80). Sex differences were also investigated. Carotid-femoral pulse wave velocity (cf-PWV) assessed via Doppler Ultrasound, blood pressure, and heart rate were collected at 6am and 9pm, at rest and during acute sympathetic activation triggered by handgrip exercise. Cf-PWV values were lower in the morning compared to the evening in all groups (p<0.01) at rest, and lower (p=0.008) in H18-30 but similar (p>0.267) in the older groups during sympathetic activation. At rest, cf-PWV values were lower in young women compared to young men (p=0.001), but this trend reversed in the older groups (p<0.04). During sympathetic activation, the cf-PWV was lower in women in H18-30 (p=0.001), similar between sexes in H50-80 (p=0.122), and higher in women in T2DM50-80 (p=0.004). These data do not support the hypothesis that aortic stiffness is increased in the morning compared to the evening within any of the considered groups, in both rest and sympathetic activation conditions. There are differences between sexes, which vary according to age and diabetes status. In particular, aortic stiffness is higher in older women compared to men with diabetes during acute stress.